Ultimate shark rumble - Pallotta, Jerry (Pallotta, Jerry. Who would win?, 2020)
"This nonfiction reader compares and contrasts 16 ferocious sharks. Readers will learn about each animal's anatomy, behavior, and more. Then compare and contrast the battling animals before finally discovering the winner! This nonfiction series is full of facts, photos, and realistic illustrations, and it includes a range of mammals, sea creatures, insects, and dinosaurs to satisfy all kinds of animal fans." --